A Synergistic Effect of Moringa oleifera-Based Coagulant and Ultrafiltration for the Wastewater Treatment Collected from Final ETP - Ashita Rai; Abdelfattah Amari; Virendra Kumar Yadav; Mohamed A. Ismail; Noureddine Elboughdiri; M. H. Fulekar; Anup Basnet (Adsorption Science & Technology)
Provision of safe drinking water, devoid of aetiologies, is an all-time challenge due to the usage of unsafe chemicals in most of the water treatment processes. The main objective of the present paper is to evaluate the use of Moringa oleifera (MO) as a natural coagulant in coagulation/flocculation (C/F) followed by the ultrafiltration (UF) of Final Effluent Treatment Plant wastewater treatment which can also be employed as an alternative to the present conventional methods of treatment. Process efficiency was evaluated in terms of chemical oxygen demand (COD), biochemical oxygen demand (BOD), turbidity, total hardness, alkalinity, ammoniacal nitrogen, and zeta potential along with permeability and fouling behaviour of the membrane. A significant improvement in both the physical and chemical characteristics of the effluent quality is showing a clearer colour and a greater reduction in BOD (89.74%) and COD (63.80%) values, while pH was in the acceptable range for effluent disposal. The results indicate a lower membrane fouling rate (49%), an increase in permeate flow, and better quality of the permeate, proving that the C/F-UF treatment is an effective and efficient technique for wastewater treatment. Eventually, the treated wastewater obtained with this process generates better quality water and preserves the aquatic ecosystem.